2018
DOI: 10.1007/s10068-018-0511-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the volatile profile of wax apple (Syzygium samarangense) wines fermented with different commercial Saccharomyces cerevisiae strains

Abstract: The effect of four commercial Saccharomyces cerevisiae strains (D254, VIC, BV818, and RV100) on the volatile profile of wax apple (Syzygium samarangense) wine was investigated in this study. Alcohols and esters were the most two abundant groups of identified volatiles in wax apple wines. However, different S. cerevisiae strains possess various capacities in releasing/synthesizing volatiles with varied mRNA levels of genes involved in volatiles metabolism during wax apple wine fermentation. VIC, which yielded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Ethyl butyrate was previously reported to be the predominant aroma component of mature A. arguta fruits [ 61 ] and was also detected in this study. These esters provide apple, pineapple, banana, strawberry, cheese, sour, brandy, and floral flavors [ 23 , 33 , 35 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl butyrate was previously reported to be the predominant aroma component of mature A. arguta fruits [ 61 ] and was also detected in this study. These esters provide apple, pineapple, banana, strawberry, cheese, sour, brandy, and floral flavors [ 23 , 33 , 35 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been reported that the production of fatty acids is dependent on the yeast strains and their abilities to synthesize/convert precursors or break carbon chains [ 45 ]. These varying abilities could explain the differences in acids observed when different yeast strains were used ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Diacetyl and acetoin in the samples were analyzed by GC-MS as previously described by Lin et al (2019) . The separation, detection, and quantification of volatile compounds were performed on a GC-MS system (5977B GC/MSD, Agilent, United States) coupled with PAL3 Series II autosampler systems (Agilent, United States) and equipped with an HP-INNOWAX capillary column (60 m × 0.25 mm inner diameter, 0.25 μm film thickness, Agilent, United States).…”
Section: Methodsmentioning
confidence: 99%